2008
DOI: 10.3324/haematol.12603
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of copy number changes and loss of heterozygosity in myelodysplastic syndrome with del(5q) using high-density single nucleotide polymorphism arrays

Abstract: BackgroundWe undertook a genome wide single nucleotide polymorphism analysis of a spectrum of patients with myelodysplastic syndrome del(5q) in order to investigate whether additional genomic abnormalities occur. Single nucleotide polymorphism array analysis has been shown to detect not only gene deletions but also regions of uniparental disomy that can pinpoint particular regions for mutation analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 27 publications
5
25
0
1
Order By: Relevance
“…2 This is reflected in its relatively good prognosis. 8,11 Previous studies have shown mutations in a limited number of genes, including TP53, JAK2 and ASXL1 9,10,34,46 in this subtype of MDS.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 3 more Smart Citations
“…2 This is reflected in its relatively good prognosis. 8,11 Previous studies have shown mutations in a limited number of genes, including TP53, JAK2 and ASXL1 9,10,34,46 in this subtype of MDS.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…2 The results of the analysis are listed in Online Supplementary Table S5. The del(5q) was characterized in all 33 cases.…”
Section: Copy Number Changes and Uniparental Disomy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A common deleted region (CDR) has been identified covering the area of 5q31-32, where two alternative missing segments have been reported, one proximal deleted entity associated with advanced MDS conditions and a second distal deleted region associated with the 5q-deletion syndrome with better prognosis (9). Loss of the CDR region ablates 44 genes and results in haploinsufficiency conditions for many of these gene products, where the levels of gene products are not sufficient for the physiological cell function.…”
Section: Introductionmentioning
confidence: 99%